The The Correlation of Community Knowledge and Behavior Toward The Covid-19 Vaccine in The Graha Lestari Citra Raya Housing Cluster on Desember 2021 - Hilman Kurniawan; Vernonia Yora Saki; Ekadipta (IONTech Journal, 2023)
The emergence of the Covid-19 pandemic has been able to paralyze the activities of all people who are carried out outside the home. Along with the outbreak of Covid-19 in various countries, the government is having difficulties in dealing with the real threat of Covid-19. A health program is a combination of interrelated activities that must be carried out in certain sequences. In efforts to improve public health, vaccines are an effective way to prevent disease, including vaccines intended to prevent Covid-19. The vaccination program in Indonesioa began in January 2021, the delivery of the Covid-19 vaccine was carried out in stages to the public. The purpose of this study was to determine the knowledge and behavior of the residents of Graha Lestari Citra Raya Housing toward the Covid-19 Vaccine. This type of research is quantitative using descriptive method. The sampling technique used is purposive sampling. The results of this study indicate that the level of knowledge of the residents of Graha Lestari Citra Raya Housing about the Covid-19 vaccine has good knowledge of 64 people with a percentage (69.57%). The results of the study for the attitude of residents of the Graha Lestari Citra raya Housing towards the Covid-19 vaccine had a good attitude as many as 59 people with a percentage (64.13%). The results of the relationship between knowledge and the attitude of the residents of Graha Lestari Citra Raya Housing toward the Covid-19 vaccine resulted in p value of 0.001, this shows that there is a significant relationship between knowledge and attitude. It was concluded that residents have good knowledge and attitudes towards the Covid-19 vaccine. The citizens can increase information of the Covid-19 vaccine through available information media.